The relation of walking forces to structural damage in the knee: The Multicenter Osteoarthritis Study - Sara, Lauren K.; Felson, David T.; Tilley, Sarah; LaValley, Michael P.; Lewis, Cora E.; Lynch, John A.; Segal, Neil A.; Guermazi, Ali; Roemer, Frank; Stefanik, Joshua J.; Lewis, Cara L. (Osteoarthritis and Cartilage, 2025)
Objective: Mechanical loading is an important, modifiable risk factor for knee osteoarthritis. Identifying walking loads associated with disease worsening presents intervention opportunities. Our purpose was to evaluate the longitudinal relation of the baseline vertical ground reaction force (GRF) during walking to worsening bone marrow lesions (BMLs) and cartilage damage using cohort data from the Multicenter Osteoarthritis Study (MOST). Methods: MOST participants with GRF data at baseline and magnetic resonance imaging examinations at baseline and 2-year follow-up were included. Peak impact force (PIF) and average loading rate (ALR) from the vertical GRF were analyzed with respect to four joint regions (i.e., the medial and lateral portions of the tibiofemoral and patellofemoral joints). Analyses used logistic regression with generalized estimating equations and adjusted for relevant covariates. Results: Higher PIF was associated with increased odds of worsening BMLs in the lateral patellofemoral joint (odds ratio (95% confidence interval [CI]): 1.33 (1.11, 1.60)) and worsening cartilage damage in the lateral patellofemoral joint (1.48 (1.24, 1.77)), lateral tibiofemoral joint (1.24 (1.03, 1.50)), and medial tibiofemoral joint (1.25 (1.06, 1.48)). Higher ALR was associated with reduced odds of BML worsening in the lateral tibiofemoral joint (0.60 (0.41,0.87)). Conclusions: Higher peak forces when walking were associated with worsening BMLs in the lateral patellofemoral joint and with worsening cartilage damage in regions of the knee associated with higher contact forces during walking. Higher ALRs were not associated with increased odds of structural worsening (BMLs or cartilage).
CRIS-Team Scopus Importer:2025-05-02
Keywords: Bone marrow lesions; Cartilage; Ground reaction force; Impact; Loading rate; MRI